Analisis SWOT Lembaga Pendidikan Tinggi Islam (Studi Kasus Universitas Islam Zainul Hasan Genggong Program Studi PIAUD Kraksaan-Probolinggo) - Ja’far Shodiq; Nuril Alfiyah (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
SWOT analysis is a method for describing conditions and evaluating a problem, project or business concept based on external and internal factors, namely strengths, opportunities, weaknesses. SWOT analysis is part of the strategic planning stages of an organization which consists of three stages, namely: the data collection stage, the analysis stage, and the decision making stage. In the data collection stage, it can be done by analyzing the state of the organization both internally and externally. The next step is to utilize all of this information in strategic formulation models for study programs. One of the problem solving models that can be used is the SWOT matrix model After conducting a SWOT analysis at UNZAH, several examples of strategic study program steps can be put forward for quality improvement, including: Develop study programs based on Islamic boarding schools according to the needs of the community who want character building, Utilize technology for marketing education, Increase quality graduates in the fields of religion and academics so that the community believes in the quality of UNZAH and seeks funds from donors and other businesses to support study program development.